Interest In The Influence Of The Pegadaian Digital Service (PDS) Application On Customers At Pt Pegadaian Ciparay Branch, Bandung Regency - Adji, Widwi Handari; basit, Firan abdul (Pascasarjana STIE Miftahul Huda, 2025)
The digitalization process in Indonesia is accelerating rapidly in the economic sector, impacting various sectors of life, including banking and finance. The purpose of this study is to determine whether there is a correlation between each user's use of the pawnshop application.Cronbach'sDigital Service. To facilitate, the researcher will take a number of certain people who are intentionally selected who actively use the application and are willing to fill out the questionnaire. Data collection instruments, namely primary and secondary primary data are collected through filling out questionnaires and observations to analyze this research the author uses software in the form of SPSS version 30. The data to be collected using the questionnaire questionnaire is forwarded to customers. in the table above through the results of the reliability test with Cronbach's alpha is known in the variable (X) which is 0.922 and the results of the variable test (Y) which is 0.938. From these two variables, the Cronbach alpha value must be greater, all instrument results get a score of more than 0.60, while the results of the t test and f test show the existence of a strong and significant relationship between the use of PDS and the use of customer interest, therefore, it can be concluded that the easier and more convenient this application is used, the higher the customer interest in utilizing digital pawnshop services.